Chromatin assembly factor 1 is essential and couples chromatin assembly to DNA replication in vivo - Hoek, Maarten (National Academy of Sciences, 2003)
De novo chromatin assembly maintains histone density on the daughter strands in the wake of the replication fork. The heterotrimer chromatin assembly factor 1 (CAF-1) couples DNA replication to histone deposition in vitro, but is not essential for yeast cell proliferation. Depletion of CAF-1 in human cell lines demonstrated that CAF-1 was required for efficient progression through S-phase. Cells lacking CAF-1 accumulated in early and mid S-phase and replicated DNA slowly. The checkpoint kinase Chk1, but not Chk2, was phosphorylated in response to CAF-1 depletion, consistent with a DNA replication defect. CAF-1-depleted cell extracts completely lacked DNA replication-coupled chromatin assembly activity, suggesting that CAF-1 is required for efficient S-phase progression in human cells. These results indicate that, in contrast to yeast, human CAF-1 is necessary for coupling chromatin assembly with DNA replication.